Performance pay and prior learning: evidence from a retail chain - Manthei, Kathrin; Sliwka, Dirk; Vogelsang, Timo (Bonn, 2018)
"We run two field experiments within a large retail chain showing that the effectiveness of performance pay crucially hinges on prior job experience. Introducing sales-based performance pay for district- and later for store-managers, we find negligible average treatment effects. Based on surveys and interviews, we develop a formal model demonstrating that the effect of performance pay decreases with experience and may even vanish in the limit. We provide empirical evidence in line with this hypothesis, for instance, finding positive treatment effects (only) in stores with low job experience."